FINITE ELEMENT MODELLING OF STEEL POLES FOR POWER PRODUCTION AND TRANSMISSIONS (Nigerian Journal of Technology, 2019)
Materials used in civil engineering constructions display wide range in their engineering properties; a structural engineer is required to quantify the risks and advantages of using such materials. Continuous supply of electricity is essential for every nation and electric poles are been susceptible to extreme damages caused by natural hazards such as snow, wind, ice, earthquake etc. These actions can knock down poles thereby causing damage and disruption of power supply. Selecting a pole material such as steel for power transmissions will sufficiently help in distributing power due to its superior material properties. The determination of the response of the steel poles to loads is accomplished by the aid of Finite Element (FE) coded in software, ABAQUS CAE. The extent of damage as a result of deflections as per stresses and displacements were effectively measured and simulated in the software. The result in ABAQUS shows that the steel poles will not suffer any reasonable deformation when loaded indicating that steel poles material properties are sufficient to provide adequate resistance against actions such as deformations and deflections during their service lives. http://dx.doi.org/10.4314/njt.v38i4.4